Dynamic analysis of the wind-wave-current-bridge system considering pile-soil interaction. Issue 15 (November 2022) - Han, Jiayi; Pan, Liang; Lu, Baojie; Zhang, Zhen; Bi, Xinyu; Zhu, Bing
Coastal bridges are normally confronted with a complex marine environment including wind, wave and current. Present researches rarely take the current action and pile-soil interaction into consideration. It is thus essential to conduct the dynamic analysis of the cable-stayed bridge under wind-wave-current action considering pile-soil interaction. A coupled wind-wave-current-bridge (WWCB) system is proposed in this study to help understand the bridge dynamic performance. In the WWCB system, the bridge model is established through the finite element method, and the pile-soil interaction is considered through the pile-soil solid contact (PSSC) model. The wave-current action is obtained through a numerical wave tank, while the wind is simulated as the stochastic random process and generated with spectrums. The initial geostress, mass and density distribution are also considered in the WWCB system. To illustrate the bridge dynamic characteristics, dynamic responses under different load combinations are presented. Furthermore, the natural frequency and spectral density function comparison between the consolidation model, PSSC model and soil-spring model are provided to investigate the influence of the pile-soil interaction. The results show that different from previous conclusions, the wave-current action plays the dominant role instead of the wind action in some cases when considering the pile-soil interaction. Additionally, the consideration of the pile-soil interaction would decrease the structural stiffness, resulting in lower natural frequencies and wider frequency distribution. Consequently, the influence of the wave-current action and pile-soil interaction should be noted in the practical engineering.